PENGARUH SARANA/PRASARANA DAN KOMITMEN TERHADAP KEPUASAN KERJA KARYAWAN PT. ARARA ABADI SINARMAS FORESTRY - Syerli Susanti; Syakdanur NAS; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to determine the facilities / infrastructure and commitment effect significant on job satisfaction at PT. Arara Abadi Sinarmas Forestry. The population in this research is all employees at PT Arara Abadi part of planting seeds as many as 160 people with 114 people who research sample is determined by simple randong sampling. Data collected in this study used questionnaire about the facilities / infrastructure, commitment, and job satisfaction are distributed to respondents. Data was analyzed using multiple linear regression analysis. In descriptive, facilities / infrastructure available inside including adequate category (80,7%), commitment to high category (89,5%), and job satisfaction to high category (72,2%). The result showed that facilities / infrastructure and commitment have a significant on the job satisfaction. Judging from the value (Rsquare) abtained a value of 0,096. The results prove that the meaning of the influance of facilities / infrastructure, commitment on job satisfaction is 9,6%. The regression equation Y=27,455+0,222X1+0,209X2.Key Words: Job Satisfaction. Facilities / infrastructure, commitment